RONC-12. Evaluation of brain network segregation using resting state functional MRI in pediatric brain tumor patients treated with proton beam therapy. (3rd June 2022) - Dowling, Anna; Seitzman, Benjamin; Mitchell, Timothy; Olufawo, Michael; Agamah, Miriam; Butler, Rachel; McMichael, Alana; Dierker, Donna; Anandarajah, Hari; Dworetsky, Ally; Coalson, Rebecca; Jiang, Catherine; et al.
Abstract: INTRODUCTION: Mechanisms of cognitive injury in pediatric brain tumor (BT) patients are poorly understood and biomarkers predicting cognitive deficits are lacking. Resting state functional MRI (rsfMRI) can evaluate large-scale brain networks to provide insight into neural changes that follow diagnosis and treatment. This project evaluated functional brain network segregation in pediatric BT patients treated with proton beam radiation therapy (PBRT). METHODS: rsfMRI scans were acquired from 21 pediatric patients (5 female, 16 male) with any brain tumor diagnosis treated with PBRT. Data were processed to reduce contamination, and correlation matrices were generated using all gray matter voxels. Brain network segregation (BNS) was measured and compared to 139 age-matched controls. Analysis included comparison of BNS in association systems (comprised of default mode, frontoparietal, dorsal attention, language, salience, and cingulo-opercular networks) and somatosensory systems (including auditory, visual, and somatomotor networks). Patient and clinical factors were evaluated for relationships with BNS. Patients underwent cognitive testing utilizing the NIH Toolbox Cognitive Domain (NIH-TCD). RESULTS: Median age at PBRT was 10 years (range 2.2-17.9). PBRT volume was whole brain in 10 and conformal in 11. rsfMRI occurred at a median of 2.9 years (range 1.0-5.6) after PBRT. Average BNS of association systems was significantly lower in patients than in controls (t= -8.1, p<10 -10 ), but there was no significant difference in BNS of somatosensory systems (p=0.4). There was a trend towards worse BNS in association systems in patients <10 years old at PBRT (p=0.07). Patients demonstrated deficits in cognitive testing as assessed by the NIH-TCD; however, there were no significant relationships between score and network segregation. CONCLUSION: Pediatric BT patients treated with PBRT demonstrated normal BNS in somatosensory systems. However, BNS of association systems, which control high-level cognitive functions including social cognition, attention, and memory formation, was significantly decreased in BT patients treated with PBRT.